WO3-x/Si n-n homotype heterojunction with high performance photodetection characteristics. (December 2020) - Zhang, Xiwei; Su, Yiwen; Tang, Zhenjie; Hu, Dan; Wang, Zhi; Hou, Yuexin; Wang, Xinmiao
Abstract: WO3 has a great potential in the field of optoelectronics. Herein, sub-stoichiometric WO3-x thin film is prepared and WO3-x /Si n-n homotype heterojunction with pronounced rectifying behavior is constructed. Moreover, the heterojunction exhibits excellent photodetection characteristics, including a large responsivity of 72.8 A/W, a high specific detectivity of 3.96 × 10 11 Jones and fast response times of 5.8 μs/1.27 ms. The mechanism of photoinduced charge separation and transfer in the WO3-x /Si n-n homotype heterojunction is analyzed by Kelivn probe force microscopy. These results suggest that the WO3-x /Si n-n homotype heterojunction is of excellent performance in the field of optoelectronic application. Graphical abstract: Image, graphical abstract